Comparison of Unilateral Middle Cerebral Artery and Bilateral Middle Cerebral Artery Monitoring for Right-to-Left Shunt Detection by Contrast-Enhanced Transcranial Doppler - Zhang, Wenjie; Yang, Le; Wang, Shuli; Wang, Lin; Li, Haixian; Yang, Keshi (Frontiers in Neurology, 2022)
Introduction Contrast-enhanced transcranial Doppler (c-TCD) is a noninvasive test with high sensitivity for the detection of a right-to-left shunt (RLS). Currently, there are no reports on the outcomes of unilateral versus bilateral middle cerebral artery (MCA) monitoring. This study compared the positivity rate of bilateral MCA monitoring with unilateral MCA monitoring for RLS using c-TCD. Methods We enrolled 239 patients (86 women and 153 men) with a mean age of 48.54 ± 13.25 years (range, 14–79 years), who underwent c-TCD examination in the Department of Transcranial Doppler Ultrasound of our hospital between February 2018 and February 2021, due to suspicion of RLS. Bilateral MCA monitoring of 239 patients was performed using dual-channel and dual-depth c-TCD. The positive rate and shunt classification of RLS were calculated for left, right, and bilateral MCA monitoring. The differences in RLS detected by c-TCD monitoring of the left, right and bilateral MCA were compared. Results In the left middle cerebral artery (LMCA) monitoring, 35.56% (85 of 239) had a positive RLS result, 38 cases were permanent (44.70%), and 47 cases were latent (55.30%). In the right middle cerebral artery (RMCA) monitoring, 36.82% (88 of 239) had a positive RLS result, 38 cases were permanent (43.18%), and 50 cases were latent (56.82%). In the bilateral MCA group, 43.09% (103 of 239) had a positive RLS result, 50 cases were permanent (48.54%) and 53 were latent (51.46%). The positive rate of bilateral MCA monitoring was higher than that of LMCA and RMCA (43.09, 35.56, and 36.82%, respectively), and the difference was not statistically significant (P = 0.193). The positive rate of bilateral MCA monitoring was higher than that of LMCA and RMCA for mild and moderate shunts, but the difference was not statistically significant. The positive rate of bilateral MCA monitoring was equal to that of RMCA, but higher than that of LMCA, with no statistical significance. LMCA monitoring revealed 85 patients with RLS. The sensitivity was 82.52% (85/103). The specificity was 100%. The RMCA monitoring results showed 88 cases with RLS. The sensitivity was 85.44% (88/103). The specificity was 100%. Conclusions There was no significant difference in the RLS detection rate between unilateral and bilateral MCA monitoring using c-TCD. Bilateral MCA monitoring may be more advantageous for mild RLS detection.